Tc-99m-ECD SPECT as the measure for therapeutic response in patients with cobalamin deficiency: Two case reports. Issue 39 (September 2016) - Tu, Min-Chien; Lo, Chung-Ping; Chen, Ching-Yuan
Abstract: Background: Cobalamin (Cbl) is an essential vitamin for human health. While an increasing body of evidence supports the negative impact of Cbl deficiency on cognition, the causality has yet to be determined, and the reported therapeutic responses after Cbl supplement therapy have been inconsistent. Besides, few reports have described neuroimaging characteristics associated with the therapeutic response. Methods: To describe and compare technetium-99m ethyl cysteinate dimer single-photon emission computed tomography (Tc-99m-ECD SPECT) findings in 2 patients with Cbl deficiency with distinct therapeutic responses. Results: Case 1 scored 12/30 in the mini-mental state examination (MMSE) and 34/100 in the cognitive abilities screening instrument (CASI). Profound deficits in mental manipulation, drawing, short-term/long-term memory, and verbal fluency were noted. Case 2 scored 24/30 in the MMSE and 78/100 in the CASI, mainly due to impaired mental manipulation, abstract thinking, and borderline performance in short-term memory and verbal fluency. While both cases showed widespread hypoperfusion within bilateral frontotemporal regions and thalamus on Tc-99m-ECD SPECT, Case 2 demonstrated relatively preserved radio-uptake in the frontal regions, especially the anterior cingulate cortex (ACC) and prefrontal cortex (PFC), consistent with the better therapeutic response ( Case 1 : 12/30 to 11/30 in the MMSE; Case 2 : 24/30 to 28/30 in the MMSE). Conclusion: Given that the ACC integrates the limbic system and frontosubcortical circuits and the PFC governs executive function, the extent and severity of hypofrontality may be responsible for the worse prognosis. Our Tc-99m-ECD SPECT observations revealed that the negative impact on cerebral metabolic tone is relevant to the severity of Cbl deficiency, and the functional integrity of the ACC and PFC is highly associated with the preservation of global cognitive function in our cases with Cbl deficiency.